Peace And Land in The Context of The Exercise of The Colombian Civil Sphere - Ramírez Orozco, Sandra Ligia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This study seeks to show how land tenure in Colombia represents a historical difficulty for the exercise of the civil sphere and the achievement of peace. This is how, based on the theoretical contributions of authors such as Jeffrey C. Alexander and Johan Galtung, an approach to the interpretation, analysis, and understanding of the consequences of the post-conflict sociocultural trauma that violence leaves in those displaced by this social phenomenon. In this way, the 2016 Havana agreement has as one of its most important objectives in point one, the restitution of lands fairly and equitably as a demonstration of the governmental and social will about the search for peace.